The Long, Angry Summer of ’43: Labour Relations in Quebec’s Shipbuilding Industry - Pritchard, James (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2010)
Abstract The complex story of labour unrest in Quebec’s shipbuilding industry considerably broadens understanding of Canada’s wartime industrial relations. For while trade union leaders were significant in organizing thousands of shipyard workers, and government and business opposition were givens, workers sometimes struggled in the absence of leadership to achieve their goals and inter-union conflict frequently obstructed their eﬀorts. The spontaneity of worker struggle in Quebec shipyards was less due to union weakness, however, than to conflict between craft versus industrial-based trade unionism. Strikes in Quebec’s shipbuilding plants during 1943 also shed light on the growing failure of the Canadian government’s labour policy known as compulsory conciliation. The contextualization of labour relations in Quebec’s shipyards during that long, angry summer lends support to those historians who argue that workers’ struggle rather than politicians’ acuity had a greater impact on the eventual appearance of pc 1003 than others would allow.